2013
DOI: 10.1158/0008-5472.can-13-0677
|View full text |Cite
|
Sign up to set email alerts
|

MUC1 Is a Potential Target for the Treatment of Acute Myeloid Leukemia Stem Cells

Abstract: Acute myeloid leukemia (AML) is a malignancy of stem cells with an unlimited capacity for self-renewal. MUC1 is a secreted, oncogenic mucin that is expressed aberrantly in AML blasts, but its potential uses to target AML stem cells have not been explored. Here we report that MUC1 is highly expressed on AML CD34+/lineage−/CD38− cells as compared to their normal stem cell counterparts. MUC1 expression was not restricted to AML CD34+ populations as similar results were obtained with leukemic cells from patients w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 34 publications
3
54
0
Order By: Relevance
“…14,15 Notably, treatment of MM and AML cells with MUC1-C inhibitors has been associated with increases in ROS and thereby cell death in vitro and in xenograft models. [15][16][17] Here, we demonstrate that MUC1 is overexpressed in CTCL cell lines in comparison with B-cell lymphoma cell lines and normal T cells. Investigation of primary CTCL cells confirmed high levels of MUC1 expression in the malignant T-cell population, in contrast to T cells from normal individuals.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…14,15 Notably, treatment of MM and AML cells with MUC1-C inhibitors has been associated with increases in ROS and thereby cell death in vitro and in xenograft models. [15][16][17] Here, we demonstrate that MUC1 is overexpressed in CTCL cell lines in comparison with B-cell lymphoma cell lines and normal T cells. Investigation of primary CTCL cells confirmed high levels of MUC1 expression in the malignant T-cell population, in contrast to T cells from normal individuals.…”
Section: Introductionmentioning
confidence: 61%
“…16,17 Briefly, cells were incubated with monoclonal antibody (mAb) DF3 (anti-MUC1-N) or a control mouse immunoglobulin (Ig) G1 for 30 minutes, followed by secondary labeling of the cells with phycoerythrin-conjugated goat anti-mouse IgG for an additional 30 minutes. Stained cells were analyzed by flow cytometry using FACScan and CellQuest Pro software (BD Biosciences).…”
Section: Detection Of Muc1 Expression By Flow Cytometrymentioning
confidence: 99%
“…25,26 Significantly, treatment of AML cell lines and blasts with MUC1-C inhibitors is associated with growth inhibition and death induction. 19,27 These findings provided support for the dependence of AML cells on MUC1-C for their survival.…”
Section: Introductionmentioning
confidence: 63%
“…MUC1 is expressed in most if not all primary AML cells and cell lines. 19 Indeed, recent work has shown that AML stem/progenitor cells from 26 patients all express MUC1. 19 By contrast, normal hematopoietic stem cells express low to undetectable MUC1 levels.…”
Section: Targeting Muc1-c Suppresses Growth Of Primary Aml Cellsmentioning
confidence: 99%
See 1 more Smart Citation